An Effectiveness Analysis of Financial Educational Programs in Ngipik Village, Kulon Progo Yogyakarta - Dimas Bagus Wiranatakusuma (PT FORMOSA CENDEKIA GLOBAL, 2023)
Financial education is part of the approach for mitigating the effects of unanticipated financial problems. Financial education is important not only for businesses, but also for households and individuals. However, research concentrating on financial education are scarce as compared to financial planning in practice, such as investment, retirement or saving references. Financial education is, ideally, a prerequisite for financial planning skill. In our scenario, for example, residents in Ngipik village are illiterate and admit to lacking financial literacy knowledge. As a result, this article seeks to assess the effectiveness of a month-long financial education program aimed primarily at children, youth, and society in general. The results show that 72% of the targeted objects are satisfied with the programs and that they are successful in improving their financial literacy, particularly financial planning. This program, however, did not teach them using an algorithm that can recommend the ideal composition of assets gathered in order to preserve their life sustainability.